Endothelial glycocalyx integrity in oncological patients. (1st August 2022) - Keramida, Kalliopi; Thymis, John; Anastasiou, Maria; Katogiannis, Konstantinos; Kotsantis, Ioannis; Economopoulou, Panagiota; Pappa, Vassiliki; Tsirigotis, Panagiotis; Bistola, Vasiliki; Thodi, Maria; Psyrri, Amanda; Filippatos, Gerasimos; et al.
Abstract: Background: Cancer is associated with early changes in the cardiovascular system (CV) before overt cardiotoxicity. Endothelial dysfunction is induced by chemotherapeutic regimens but there is no data for endothelial glycocalyx in cancer. Methods: Sixty-four patients with cancer (65.6% with solid tumors and 34.4% with hematological malignancies) and 32 controls from the outpatient cardiology clinic were included in the study. The perfused boundary region (PBR) of the sublingual arterial microvessels, Pulse Wave Velocity (PWV) and augmentation index (AI) were measured. A standard transthoracic echocardiogram plus assessment of global longitudinal strain (GLS) of all cardiac chambers were performed. Results: There was no difference in the baseline profile (age, sex, smoking, hypertension, diabetes, hyperlipidemia and coronary artery disease) and in the echocardiographic parameters between the two groups, with the exception of left atrial volume (33.3 ± 13 in cancer patients vs 27.6 ± 6.5 ml/m 2 in controls). PBR 5–25 and PBR 20–25 were significantly increased in cancer patients vs controls (2.11 ± 0.36 vs 1.97 ± 0.21 μm, p = 0.025 and 2.65 ± 0.48 vs 2.40 ± 0.36 μm, p = 0.012, respectively). Endothelial glycocalyx thickness impairment was independent of traditional CV risk factors and anticancer therapy, but proportional to disease stage ( r = 0.337, p = 0.044). However, there was no difference in arterial stiffness between the two groups (PWV 10.74 ± 4.11 vs 11.26 ± 3.38 m/s, p = 0.539 and AI 11.28 ± 28.87 vs 15.38 ± 18.8 %, p = 0.470). Conclusions: Endothelial function as assessed by endothelial glycocalyx thickness is significantly impaired in cancer patients without overt cardiotoxicity. This implies that PBR might be useful for the early assessment of microvascular and endothelial toxicity of cancer. Highlights: Endothelial glycocalyx thickness is significantly impaired in cancer patients, even before any cancer treatment Endothelial glycocalyx impairment is proportional to cancer stage Impairment of endothelial glycocalyx is independent of anti-cancer therapies Assessment of endothelial glycocalyx integrity could be used for early identification of cardiovascular toxicity